Using arbuscular mycorrhizal fungi (Gigaspora margarita) as a growth promoter and biocontrol of leaf blight disease in eucalyptus seedlings caused by Cylindrocladium quinqueseptatum - Klinsukon, Chaiya; Ekprasert, Jindarat; Boonlue, Sophon (Rhizosphere, 2021)
The leaf blight disease is a common threat to the growth and production of eucalyptus seedlings in Thailand. This work then aimed to apply a biocontrol approach to help plants survive the disease. Cylindrocladium quinqueseptatum KKU-H4-B12, a pathogen causing leaf blight disease, was isolated from the lesion of eucalyptus leaves. Its pathogenicity was confirmed before use in the field experiments. An AMF Gigaspora margarita KKU-BH-01, previously proved to efficiently promote growth of eucalyptus, was pre-inoculated into eucalyptus seedlings for 30 days prior to pathogen infection. The results showed that an AMF could successfully colonize eucalyptus roots even in the pathogen-infected plants (≥56%). The disease assessment indicated that plants pre-inoculated with AMF and later infected with the pathogen (PM) had a disease reduction of 33.4%. Plant height, SPAD, fresh weights of roots and shoots in PM plants were relatively equal to those of the control plants, suggesting that AMF could relieve detrimental effects of the disease in plants. Moreover, we found that AMF induced plant chitinase and β-1,3-glucanase enzymes resulting in improved disease resistance in plants. This work is the first to report the application of a single AMF species to effectively enhance the growth and help eucalyptus seedlings to survive leaf blight disease.